Sportverletzungen des Nervensystems - Lang, C.; Stefan, H. (Fortschritte der Neurologie - Psychiatrie, 1999)
Almost 1% of all Germans suffer sports injuries each year, almost 5% of all peripheral nerve lesions are due to sports. A review is given on various activities detailing the specific risks for traumata of the central and peripheral nervous system. Specifically these are volleyball, handball, basketball, American football, soccer, bowling, hockey, baseball, tennis, golf, javelin, fencing, wrestling, judo, boxing, running, jumping, dancing, mountain climbing, weight lifting, gymnastics, horse-back riding, swimming, rowing, skiing, skating, shooting, (motor) biking, car racing, flying, and sports for the disabled. The knowledge of typical traumata should enable the neurologist to rapidly and reliably recognize related lesions and to contribute to their prevention or improvement.